Association between spicy food consumption and the risk of non-alcoholic fatty liver disease/metabolic dysfunction-associated steatotic liver disease and liver fibrosis - Zhao, Na; Liu, Huimin; Wang, Yan; He, Yun; Zhang, Ning; Li, Yuan (Frontiers in Nutrition, 2025)
IntroductionEvidence suggested that capsaicin may protect against steatotic liver disease (SLD), but these findings lack validation in population-based studies. This research aimed to explore the association between spicy food consumption and the risk of non-alcoholic fatty liver disease (NAFLD)/metabolic dysfunction-associated steatotic liver disease (MASLD) and liver fibrosis.MethodsA total of 23,666 participants aged 25 to 60, free from NAFLD, MASLD, and liver fibrosis, were recruited from a multi-center physical examination database in Shijiazhuang, Hebei Province, China, between 2011 and 2024. Cox proportional hazards regression model assessed the association between spicy food consumption and incident NAFLD/MASLD and advanced liver fibrosis. Restricted cubic spline (RCS) functions estimated the dose–response relationship. Subgroup and sensitive analyses evaluated heterogeneity based on various characteristics, while sensitivity analyses tested the robustness of results.ResultsThere were 42.2% of participants who reported consuming spicy food at least once per week. In this cohort study, a total of 7,965 patients with NAFLD and 7,311 patients with MASLD were identified after a median follow-up period of 12.6 years. Those who consumed spicy food more than once a week had a significantly lower risk of NAFLD/MASLD compared to non-consumers, indicating a dose–response relationship. However, this association was not observed in advanced liver fibrosis.ConclusionWeekly spicy food consumption was inversely associated with risk of incident NAFLD/MASLD, but not advanced liver fibrosis.